Role of AI in marketing through CRM integration with specific reference to chatbots - Ramaul, Laavanya (2021)
Due to digitalization, consumers are aware of the multitudes of choices and demand constant engagement and a personalized experience. Additionally, this has encouraged organizations to ensure seamless communication across various customer channels utilized to make a purchase decision. CRM is the monitoring and analysis of customer-firm relationships with the final goal of increasing sales, improving marketing strategies, and providing better customer services. AI tools such as chatbots are used to provide quick and fast responses thus creating engagement with the customers and aiding in the value creation process for the customers and firms. Additionally, chatbots provide opportunities and challenges to the organization that implements them. Previous research on chatbots has limited its scope to understanding the customer perspective. This study investigates the extent of engagement a chatbot provides and the impact of its implementation on the firms. Data is collected through ten semi-structured interviews which include companies utilizing chatbots as well as chatbot providers across two countries, Finland, and India. The findings indicate organizations are utilizing chatbots as part of their customer service in the CRM activities whereas chatbot providers emphasize its use in marketing and sales functions such as lead generation and personalized messaging. Furthermore, chatbots provide automated personalized communication in contrast to traditional mediums like emails. Chatbots can ensure connection, interaction, and satisfaction to some extent which are important aspects for customer engagement. Additionally, the implementation of chatbots provides advantages in the form of operational efficiencies and support to existing personnel and disadvantages such as technical, organizational, and regulatory challenges. Future research could investigate the effects of the pandemic on the adoption of chatbots as it will accelerate the process of digital transformation for organizations.